Acceleration of Islamic Bank Financing in Indonesian Agriculture Sector - Mubarok, Faizul (Shirkah: Journal of Economics and Business, 2021)
Economic instability is a challenge for Islamic banks in channeling financing to various sectors including agriculture. This study aims to shed some light on the influence of economic indicators and the financing response to agriculture sector using monthly data from 2006 to 2020, including data from agriculture sector financing, interest rates, inflation, exchange rates, Islamic stock index, and composite stock index. This study employed Vector Error Correction Model (VECM) method. The results revealed that only interest rates and inflation affected Islamic bank financing in the short and long term period. Islamic bank financing in the agriculture sector reached the fastest stability when responding to exchange rate shocks. The results further showed that interest rates mostly influenced the level of diversity in Islamic bank financing in the agriculture sector. The results suggest that stakeholders need to play a crucial role in stabilizing economic turmoil to accelerate Islamic bank financing particularly in agriculture sector.